2006
DOI: 10.1111/j.1747-0765.2006.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural land-use change and forest fire on N2O emission from tropical peatlands, Central Kalimantan, Indonesia

Abstract: Nitrous oxide (N 2 O) fluxes from tropical peatland soils were measured at a grassland, three croplands, a natural forest, a burned forest and a regenerated forest in Central Kalimantan, Indonesia. Only croplands received fertilization (665-1278 kg N ha −1 year −1 ). Mean annual N 2 O emissions from croplands were 21-131 kg N ha −1 year −1 in 2002-2003 and 52-259 kg N ha −1 year −1 in 2003-2004, and were significantly higher than the emissions from other comparable sites. Cropland N 2 O emissions were among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
162
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(192 citation statements)
references
References 15 publications
26
162
3
1
Order By: Relevance
“…than in oil-palm plantations (47). We are aware of only one study that found large differences in N 2 O emissions between three highly fertilized crop fields and peat forest (51). The authors found differences of 192.5, 34, and 114.5 kg of N per hectare per year, that is to say, 90.1, 15.9, and 53.6 Mg of CO 2 eq: per hectare per year.…”
Section: Land-use Dynamics and Ghg Emissions In Tropical Peatlandsmentioning
confidence: 96%
“…than in oil-palm plantations (47). We are aware of only one study that found large differences in N 2 O emissions between three highly fertilized crop fields and peat forest (51). The authors found differences of 192.5, 34, and 114.5 kg of N per hectare per year, that is to say, 90.1, 15.9, and 53.6 Mg of CO 2 eq: per hectare per year.…”
Section: Land-use Dynamics and Ghg Emissions In Tropical Peatlandsmentioning
confidence: 96%
“…However, N 2 O emission from agricultural tropical peatland is reported to be much more variable. The values have been estimated to range from À1.1 to 259 kg N ha À1 year À1 (Terry et al 1981;Inubushi et al 2003;Hadi et al 2005;Takakai et al 2006;Melling et al 2007). It is also reported N 2 O emission increased following change in land use from natural peat swamp forest to drained or burned peatland, and to agricultural peatland (Takakai et al 2006;Melling et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Nitrous oxide emission from agricultural land has been estimated to be 21.6% (3.6 Tg N year À1 ) of total global emission of N 2 O (16.2 Tg N year À1 ) (IPCC 1995). There are, however, several studies documenting N 2 O emissions not only from natural tropical peatlands, but also those under cultivation (Terry et al 1981;Inubushi et al 2003;Hadi et al 2005;Takakai et al 2006;Melling et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate of annual N 2 O emission from acacia plantation soils was comparable to those from Amazon at 0.94 kg-N ha -1 (Verchot et al 1999) or 0.80 kg-N ha -1 (Palm et al 2002), but relatively low compared with those from Southern Sumatran forests at 1.47 and 1.80 kg-N ha -1 (Verchot et al 2006) and croplands in Central Kalimantan estimated at 21-259 kg-N ha -1 (Takakai 2006). Because of the spread of acacia and other leguminous tree plantations in Asia (FAO 2001), the importance of N 2 O emissions from leguminous tree stands will increase in coming decades.…”
Section: Introductionmentioning
confidence: 79%